Virulence of Heterorhabditis bacteriophora strain HP88 (Rhabditida: Heterorhabditidae) against Stomoxys calcitrans (Diptera: Muscidae) larvae in filtercake diet.] - Monteiro Sobrinho, Américo de Castro; Mendes, Camila de Oliveira Ferreira; Leal, Luís Carlos de Souza Rodrigues; Bittencourt, Avelino José (Brazilian Journal of Veterinary Medicine, 2016)
Economic losses caused by Stomoxys calcitrans are estimated at billions of dollars worldwide, with losses in Brazil being exacerbated by the large volume of byproducts of the sugarcane and alcohol industry, which serve as a development medium for the dipteran, especially the filter cake. In this context, entomopathogenic nematodes (EPN) appear as a biological control alternative. This work aimed to evaluate the action of the nematode Heterorhabditis bacteriophora - isolate HP88 on S. calcitrans larvae in the filter cake. In the laboratory, groups of five larvae were deposited in Petri dishes containing four grams of the filter cake. Concentrations of 25, 50, 100, 150 and 200 EPN /larvae of S. calcitrans, immersed in four milliliters of distilled water, were added to the Petri dishes. In the control group, there were no nematodes, only filter cake and distilled water. The dishes were sealed with PARAFILM®, and stored in a climatized chamber at 27±1°C and 70-80% relative humidity. The experiment was observed daily with six replicates. It was verified that the mortality of all the treated groups was superior to the one that occurred in the control group (6.6%). The mortality rate in the presence of 200 EPN/larvae was 83.3%; higher than that caused by 150 EPN/larvae (76.6%), although they did not differ statistically. Mortality due to other concentrations was 38.3%, 64%, and 63.3% in groups 25, 50 and 100EPN/larvae, respectively. When the control and 25 EPN/larvae group results were compared, mean mortality was significantly different. The study concluded that entomopathogenic nematodes are efficient in the control of S. calcitrans larvae reared in medium containing filter cake.